Front Cover: Six‐Step Continuous Flow Synthesis of Diclofenac Sodium via Cascade Etherification/Smiles Rearrangement Strategy: Tackling the Issues of Batch Processing (Chem. Eur. J. 45/2022). Issue 45 (21st July 2022) - Wang, Lulu; Liu, Minjie; Jiang, Meifen; Wan, Li; Li, Weijian; Cheng, Dang; Chen, Fener
Abstract : Go with the flow : A six‐step, continuous‐flow synthesis of diclofenac sodium from commercially available aniline and chloroacetic acid was realized in a desktop microchemical plant. Diclofenac sodium was obtained in 63 % overall yield in a total reaction time of 205 min, with an average yield of above 90 % for each step. More information can be found in the Research Article by D. Cheng, F. Chen, and co‐workers (DOI: 10.1002/chem.202201420 ).